Non-loadbearing light steel framing walls under fire - Khetata, Mohamed S. (2020)
The light steel frame (LSF) construction technology started to be widely used in different types of buildings, replacing the traditional construction methods due to its light weight characteristics. Steel is recycled, dimensional stable, and ease of installation. LSF and prefabricated panels are widely used in non-loadbearing walls. The LSF walls are usually made with studs and tracks that require fire protection, normally achieved by a single plasterboard, by composite plates, or by insulation of the cavity. The partition walls are fire rated for the integrity (E) and insulation (I). The insulation capacity (I) is the ability of the element of construction to withstand fire exposure by side, without the transmission of significant heat to the unexposed side. Six fire tests were developed to define the fire resistance according to EN1363-1 [1] and EN1364-1 [2], with the main objective to evaluate the influence of the protection layers and the influence of the cavity insulation material. Numerical models are also validated with experimental tests.